Kinematic and dynamic analysis of a hexapod pronking gait robot and control actions - Soyguder, Servet; Alli, Hasan (My University, 2012)
This in this study, A hexapod robot was carried out walking, running and pronking with Spring Loaded Inverted Pendulum (SLIP) model in stance phase. This is solving a natural problem in which the main goal is to enable the robot to walk, run and pronking in a stable condition regardless of the environmental conditions. In order to solve this problem, kinematic and dynamic analysis, and control actions of a hexapod robot were realized for a pronking gait in this study. In addition, the stance and flight phase dynamic structures were solved in a sequential closed loop to obtain the equation of motion for pronking gait. The hexapod robot with pronking gait was controlled by PD control algorithm. As a result, all computer simulations have shown that the proposed control actions and method are more effective and make the system control quite easy and successful. © 2012 by World Scientific Publishing Co. Pte. Ltd.
14th International Conference on Climbing and Walking Robots and the Support Technologies for Mobile Machines, CLAWAR 2011 -- 6 September 2011 through 8 September 2011 -- Paris -- 99980
Keywords: Algorithms; Computer simulation; Equations of motion; Kinematics; Mobile robots; Closed loops; Control actions; Environmental conditions; Equation of motion; Flight phase; Hexapod robots; Spring loaded inverted pendulums; System control; Computer control systems